KOORDINASI BALAI BESAR KONSERVASI SUMBER DAYA ALAM (BBKSDA) RIAU, PEMERINTAH DESA DAN LEMBAGA ADAT DALAM MENJAGA KEARIFAN LOKAL TAMAN WISATA ALAM DESA BULUH CINA TAHUN 2017-2018 - Darmansyah, Ramlan; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this study was to determine the coordination between the Riau Natural Resources Conservation Center, the Village Government and the Traditional Institutions, in maintaining local wisdom of Buluh Cina Village Nature Park in 2017-2018. Then to find out the implementation of the development program of the Buluh Cina Village Nature Tourism Park which was formed by the Riau Natural Resources Conservation Center in 2017-2018In addition, it is also to determine the inhibiting factors of the coordination of the Riau Natural Resources Conservation Center, Village Government and Traditional Institutions in maintaining local wisdom of Buluh Cina Village Nature Tourism Park. This study uses a qualitative method that describes the data descriptively. The data collection techniques used were interviews and documentation. The data source used in this study is primary data and is supported by secondary data, namely related documents. The data source used in this study is primary data and is supported by secondary data, namely related documents. The results and discussion of this research is the transfer of function from the Rimbo Tujuh Traditional Forest in Buluh Cina Village to a Conservation Area, namely a Natural Tourism Park which is managed by the Riau Natural Resources Conservation Center. This change in function was marked by the issuance of a Decree of the Minister of Forestry of 2014 concerning the Designation of the Chinese Buluh Nature Park covering an area of 963.33 Ha. There are coordination problems between stakeholders, namely the absence of formal arrangements specifically related to technical coordination. In addition, there are differences in interests in managing and maintaining the Nature Tourism Park in Buluh Cina Village by stakeholders. Apart from the problems that occur in the coordination, It can also be seen that there are several types of activities related to synchronization in managing and maintaining local wisdom of Buluh Cina Village Nature Park. There is a common goal in maintaining and developing the potential of local wisdom at Buluh Cina Village Natural Park through several programs established by the Riau Natural Resources Conservation Center. There are inhibiting factors related to coordination between the Riau Natural Resources Conservation Center, the Village Government and the Traditional Institutions, namely the dominance of the Riau Natural Resources Conservation Center, no joint arrangements related to coordination, no special budget related to the management of the Buluh Cina Village Nature Park and the non-smooth communication relationship between the Riau Natural Resources Conservation Center, the Village Government and the Traditional Institution. Keywords: Coordination, Local Wisdom, Nature Tourism Park